PENGARUH BEAUTY VLOGGER TERHADAP SOURCE CHARACTERISTICS SERTA DAMPAKNYA TERHADAP PURCHASE INTENTION - Wulan Deasy Puspita Sari Widodo; M. Kholid Mawardi (Fakultas Ilmu Administrasi Universitas Brawijaya, 2017)
This research aims to examine the influence of (1) Beauty Vlogger as Electronic Word of Mouth on Source Characteristics, (2) Beauty Vlogger as Electronic Word of Mouth on Purchase Intention, (3) and the effect of Source Characteristics on Purchase Intention from survey women in Indonesia who has prior knowledge about NYX Professional Makeup. This quantitative research uses explanatory method, with the variables of Beauty Vlogger as Electronic Word of Mouth, Source Characteristics, and Purchase Intention. The research uses 116 respondents as the sample, employing the formula by Machin and Champbell. This research uses descriptive data and path analyses. Based on the results of the research show that the effect of the variable of Beauty Vlogger as Electronic Word of Mouth (X) is significant on Source Characteristics (Z) and Purchase Intention (Y) and the effect of Source Characteristics (Z) is significant on Purchase Intention (Y). Keyword : Beauty Vlogger, Electronic Word of Mouth, Source Characteristics, Purchase Intention ABSTRAK Penelitian ini bertujuan untuk mengetahui dan menjelaskan pengaruh (1) beauty vlogger sebagai electronic word of mouth terhadap source characteristics (2) beauty vlogger sebagai electronic word of mouth terhadap purchase intention (3) source characteristics terhadap purchase intention dengan melakukan survei pada wanita di Indonesia yang mengetahui produk NYX Professional Makeup. Jenis penelitian yang dilakukan adalah penelitian eksplanatori dengan pendekatan kuantitatif serta variabel yang digunakan adalah beauty vlogger sebagai electronic word of mouth, source characteristics, dan purchase intention. Sampel yang digunakan sejumlah 116 responden yang diperoleh dari menggunakan rumus Machin dan Champbell. Analisis data yang digunakan dalam penelitian menggunakan analisis deskriptif dan analisis jalur. Berdasarkan hasil dari penelitian menunjukkan bahwa variabel beauty vlogger sebagai electronic word of mouth (X) memiliki pengaruh terhadap source characteristics (Z) dan purchase intention (Y) serta source characteristics (Z) memiliki pengaruh terhadap purchase intention (Y). Kata Kunci : Beauty Vlogger, Electronic Word of Mouth, Source Characteristics, Purchase Intention